Safety and efficacy of the Prakash method in closed reduction of anterior shoulder dislocation - Rawat, Sanjay Singh; Barwar, Rohit; Joshi, Sachin; Kumar, Anand (International Journal of Research in Orthopaedics, 2025)
Introduction: Shoulder dislocation is a frequently encountered injury in daily medical practice. Among various types of shoulder dislocations, anterior shoulder dislocation is the most prevalent. Numerous techniques have been proposed for reducing a dislocated shoulder. The objective of this study was to evaluate the efficacy and safety of the Prakash technique in treating patients with anterior shoulder dislocation who sought treatment at our hospital's emergency department. Methods: This was a prospective study conducted from March 2023 to July 2023 in the Department of Orthopedics in Government Medical College & Associated group of Hospitals, Kota. 50 shoulders fulfilling the inclusion criteria were included in this study, and observations were noted. Results: After conducting a statistical analysis, it was observed that the new reduction method proved highly effective, successfully reducing 98% of the shoulders without the need for anesthesia. The study included a total of 50 patients, among whom 8 (16%) had left-sided shoulder dislocation, and 42 (84%) had right-sided shoulder dislocation. Notably, the reduction could be accomplished on the first attempt in 45 patients (90%), while a second attempt was required in 4 patients (8%). Fortunately, no complications were observed during the course of the study. Conclusion: The Prakash method for reducing anterior shoulder dislocation has proven to be a straightforward and effective technique based on our study findings. Due to its success rate and the fact that it doesn't necessitate anesthesia, we strongly recommend that both orthopedic surgeons and emergency care providers familiarize themselves with this method. It can be a valuable addition to their skill set and provide a safe and efficient option for treating patients with anteriorly dislocated shoulders.